Apologies in Karo Language - Surbakti, Ernawati Br (Politeknik Negeri Padang, 2018)
The aim of this research is to explain the type, the strategy, the tactic and the cultural values of apologies in Karo language. The method used is qualitative descriptive in Sei Bingei sub-district as the research location. The data obtained from the in-depth interview and participant observation. Based on observation apologies in Karo language consists of (1) Apologies in Karo language can be appointed first, apologies before doing anything ( apology were made to maintain social norms in culture) such as sentabi, ersentabi, and tabik. Second, apology after making a mistake, the apology phrase used is nembah. (2) There are three strategies for an apology in Karo language. Sentabi phrase included in the first category that is an explicit expression of apology, apology spoke clearly and the regret with minor mistake category. Nembah phrase as an apology for an acknowledgment of responsibility and apologies as a promise for not repeat the same mistakes. Nembah included in more complicated category strategies or serious mistakes. Strategy for an apology in Karo language (M), are speakers use word, phrase or sentences containing appropriate performative verbs in Karo language, such as tabik, sentabi, ersentabi, persentabin, nembah, nembah-nembah, jera, robah, lepak, erkadiola, mahap, and ngalemi. In Karo language, strategies (M) are very prominent on tradition activity for opening the activity. Strategy (M) also appear in serious apology, then continued with (TJ) responsibility and regret. (3) The cultural values in apology in Karo language consist of (a) the value of harmony, (b) the value of social and cultural, (c) the value of responsibility, (d) the value of divine.